Evaluation of Awareness Levels Towards Winter Sports in Secondary School Students Studying in Different Climatic Conditions - Muhammed Fatih Bilici; Tayfun İşlen; Sebahattin Altıntaş; Sedat Okut; Dilara Ekiz; Ömer Faruk Bilici; Serkan Kızılca (Research in Sport Education and Sciences, 2024)
This study aimed to evaluate the awareness levels of secondary school students studying in different climatic conditions toward winter sports by employing a descriptive scanning model, a quantitative research method. The SPSS 22.0 package program was used to analyze the data, while normality was assessed using the Kolmogorov and Smirnov tests. One-way analysis of variance (ANOVA) and t-tests were performed for normally distributed data. In addition, the homogeneity of the variances was examined to determine between which groups the statistically significant differences occurred; since the variances did not exhibit homogeneous features, Tamhane’s T2 test, a post-hoc multiple comparison technique, was used. A significance level of p < .05 was accepted for the findings obtained from the analyses. In order to test the reliability of the scales, internal consistency coefficients (Cronbach’s alpha) were calculated, with the results presented in table format. Based on our findings, certain demographic and socioeconomic variables were observed to affect the awareness levels of secondary school students with regard to winter sports. Comparing students living in different climatic conditions, a greater awareness of winter sports was found among those residing in regions with low snowfall, where winter conditions are unsuited to winter sports. The level of awareness concerning winter sports was thus determined to vary according to education, socioeconomic situation, and demographic characteristics rather than climatic conditions